Volume Averaging Correction Factor of Several Detectors in Small Field Radiotherapy Dosimetry - Fajar Haristyo; Supriyanto Ardjo Pawiro (Journal of Medical Physics and Biophysics, 2014)
Various type of detector, such as ionization chamber, has been used in small field radiotherapy dosimetry. There is a limitation in detector’s dimension which can produce the volume averaging effect. Detector will average the measured dose because of fluence perturbation that happens in gas-filled cavity around detector’s active volume. Purpose of this study is to calculate volume averaging correction factor of some detectors. Volume averaging correction factor can be calculated using MATLAB based algorithm. The result shows that detector with the lowest volume averaging correction factor is SFD diode detector with volume averaging correction factor value is 1,0086 in 4 cm x 4 cm field size. Whereas GD-302 has the largest volume averaging correction, 1,6083 in 0,8 cm x 0,8 cm field size. The larger size of detector, the greater volume averaging correction factor will be produced. Therefore, detector with small enough dimension is required in order to minimize the effect of volume averaging.